PENYERAPAN ANGGARAN BERDASARKAN PERENCANAAN ANGGARAN, KOMPETENSI SUMBER DAYA MANUSIA, DAN KOMITMEN ORGANISASI - Fitriasuri Fitriasuri; Rika Yuliani (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2022)
This study aims to determine how to budget absorption at the KPU of South Sumatra Province is influenced by budget planning, human resource competence, and organizational commitment. This study uses primary data, and data collection is done directly by using a questionnaire. The population comprises the finance and budget department employees in 18 General Election Commission Work Units in South Sumatra Province, totaling 106 people. A sample is several 84 people determined using Slovin's formula. Researcher use a quantitative method with multiple linear regression analysis. It started with validity and reliability tests of the instrument as well as the Classical Assumption Test, which includes the normality test, multicollinearity test, and heteroscedasticity test. The results showed that even simultaneously or partially, budget planning, human resource competence, and organizational commitment positively and significantly affected budget absorption at KPU South Sumatra Province. Good budgeting will encourage the realization of a good and maximum budget. Meanwhile, poor budgeting can result in budget revisions which will slow down and complicate the completion of plans. Furthermore, qualified human resources more easily understand their main tasks and functions to encourage work implementation as planned. Then a strong organizational commitment to the members of the organization will enable them to carry out work following the values ​​and goals of the organization.